Transplantation of adipose-derived stromal cells protects functional and morphological auditory nerve integrity in a model of cochlear implantation. Issue 9 (9th June 2021) - Radeloff, Andreas; Nada, Nashwa; El Mahallawi, Trandil; Kolkaila, Enaas; Vollmer, Maike; Rak, Kristen; Hagen, Rudolf; Schendzielorz, Philipp
Abstract : Cochlear implants are considered the gold standard therapy for subjects with severe hearing loss and deafness. Cochlear implants bypass the damaged hair cells and directly stimulate spiral ganglion neurons (SGNs) of the auditory nerve. Hence, the presence of functional SGNs is crucial for speech perception in electric hearing with a cochlear implant. In deaf individuals, SGNs progressively degenerate due to the lack of neurotrophic support, normally provided by sensory cells of the inner ear. Adipose-derived stromal cells (ASCs) are known to produce neurotrophic factors. In a guinea pig model of sensory hearing loss and cochlear implantation, ASCs were autologously transplanted into the scala tympani prior to insertion of a cochlear implant on one side. Electrically evoked auditory brain stem responses (eABR) were recorded 8 weeks after cochlear implantation. At conclusion of the experiment, the cochleae were histologically evaluated. Compared to untreated control animals, transplantation of ASCs resulted in an increased number of SGNs and their peripheral neurites. In ASC-transplanted animals, mean eABR thresholds were lower and suprathreshold amplitudes larger, suggesting a larger population of intact auditory nerve fibers. Moreover, when compared to controls, amplitude-level functions of eABRs in ASC transplanted animals demonstrated steeper slopes in response to increasing interphase gaps (IPGs), indicative of better functionality of the auditory nerve. In summary, results suggest that transplantation of autologous ASCs into the deaf inner ear may have protective effects on the survival of SGNs and their peripheral processes and may thus contribute to long-term benefits in speech discrimination performance in cochlear implant subjects.